Le Terme a sud del Pretorio di Gortina. Produzione e circolazione dei contenitori da trasporto (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
The position of Crete in the middle of the Aegean sea, not far from Africa and Egypt, as from Syria and Palestine, made the city of Gortyn a focal point within the trade routes in the Eastern Mediterranean. The study of amphorae from the 2003-2006 excavations at the “Terme a sud del Pretorio”, and the necessary comparison with the large amount of material from the “Pretorio” contexts, confirm this trade network. During the hellenistic and the early roman period, Gortyn performed the role of goods storage and distribution from the West coasts to the Aegean sea, but in the mid roman imperial age played a more active role in producing and exporting goods and amphorae. In the late roman - byzantine period, in consequence of the socio-economic changes and the rising of a new capital, Constantinople, Gortyn expanded trade routes to the eastern mediterranean coasts, favouring the outside importations of goods.
Keywords: Crete; Gortyn; Amphorae; Trade Routes; Late Roman - Byzantine period